Respons Kualitas Semen Babi Terhadap Penambahan PGF2α - Aruan, Trisno Marojahan; Paputungan, Umar; Pudjihastuti, Endang (AGRI-SOSIOEKONOMI, 2023)
This study aimed to determine the response of pig semen quality to the addition of PGF2 during semen dilution. The research was conducted from August to December 2022 at one of the pig farms in Tomohon City, North Sulawesi. The study was conducted using 4 (four) variations of PGF2 doses namely 0, 20, 40, 60 μg/mL and 5 (five) repetitions. The results obtained were then tested with the One Way Anova test and if the Sig value. <0.05 then it will be continued with Duncan's Multiple Range Test. The data processed is primary data obtained during the research. There are four treatments and five repetitions conducted by the author when conducting this research. The results of the one way anova test showed that there was no effect of treatment on mass motion and conception of pig semen. The results of the one way anova test on motility showed the effect of treatment at the +60µg/100ml prostaglandin treatment level. The results of the Duncan test on the three parameters did not show a real effect of each treatment on the parameters tested. The conclusion of the addition of PGF2α as much as 20µg/mL, 40µg/mL, PGF2α as much as 20µg/mL, 40µg/mL, 60µg/mL in pig semen (Sus Scrofa) has no effect on mass movement in pig semen (Sus Scrofa) has no effect on mass movement and conception of pigs but the addition of 60µg/mL in pig semen (Sus Scrofa) has a significant effect on individual sperm movement of pigs.